Making a difference great teachers - Enterline, Sandy; Films For The Humanities & Sciences (Firm); WITF Television (Princeton, NJ : Film For The Humanities & Sciences, 2004)
Each documentary focuses on three teachers who have made a positive influence, academically or personally, on their students' lives
DVD Format
Keywords: Teachers -- Attitudes; Motivation in education